Challenges for academic organizations' legitimacy in Colombia's transition to a postconflict context. Issue 6 (13th October 2020) - Ramirez, Jacobo; Vélez‐Zapata, Claudia
Abstract : Purpose: We explore and explain how academic organizations attempt to establish legitimacy in a transition to a postconflict context, and we examine the ethical challenges that emerge from insightful approaches to formal education in such contexts. Design/methodology/approach: We use legitimacy theory to present a case study of a business school in Medellin, Colombia (herein referred to by the pseudonym BS-MED) in the empirical setting of the end of the most prolonged armed conflict in the world. Findings: We identify the mechanisms implemented by BS-MED to comply with the Colombian government's peace process and rhetoric of business profitability and the faculty members' initiatives in response to social and academic tensions. Originality/value: This study identifies the sources of the tensions and discrepancies between the regulatory and pragmatic versus moral and cultural-cognitive criteria of legitimacy in transitions to a postconflict context. This examination advances our understanding of the challenges that organizations face regarding changes to legitimacy over time. The extreme setting of our case positions academics as key players who lead the search for legitimacy. This study challenges the understandings of legitimacy in the literature on organizations, which rarely consider broader sociopolitical transitions to a peace context.